The Grim Realities of a Doctoral Student in Aotearoa - Patel, Sneh; Baisden, Troy; Yee, Grace (New Zealand Science Review, 2022)
This article explores the multifaceted challenges confronting PhD students in Aotearoa New Zealand’s universities. In contrast to the advertised three-year completion timelines, evidence reveals extended PhD durations and a disconnect between enrolments and academic opportunities. The often unrecognised hurdles faced by PhD students include financial strains stemming from low stipends that do not cover the local cost of living, difficulty accessing additional income, and ambiguous student status. The complex phase at the completion of PhD represents a separate narrative with new challenges including the end of stipend funding and a significant gap in employment prospects while waiting months for the PhD to be examined. By documenting the poorly documented difficulties and realities, the authors aim to offer insights to stakeholders and prospective PhD students, fostering awareness and advocating for improvements in the doctoral education system.